Characterisation of the aerobic bacterial flora of boid snakes: application of MALDI‐TOF mass spectrometry. (14th March 2015) - Plenz, Bastian; Schmidt, Volker; Grosse‐Herrenthey, Anke; Krüger, Monika; Pees, Michael
Abstract : The aim of this study was to identify aerobic bacterial isolates from the respiratory tract of boids with matrix‐assisted laser desorption ionisation‐time‐of‐flight mass spectrometry (MALDI‐TOF MS). From 47 boid snakes, swabs from the oral cavity, tracheal wash samples and, in cases in which postmortem examination was performed, pulmonary tissue samples were taken. Each snake was classified as having inflammation of the respiratory tract and/or oral cavity, or without evidence of inflammation based on combination of clinical, cytological and histopathological findings. Samples collected from the respiratory tract and oral cavity were inoculated onto routine media and bacteria were cultured aerobically. All morphologically distinct individual colonies obtained were analysed using MALDI‐TOF MS. Unidentified isolates detected in more than three snakes were selected for further 16S rDNA PCR and sequencing. Among all examined isolates (n=243), 49 per cent (n=119) could be sufficiently speciated using MALDI‐TOF MS. Molecular biology revealed several bacterial species that have not been previously described in reptiles. With an average of 6.3 different isolates from the respiratory tract and/or oral cavity, boids with inflammatory disease harboured significantly more bacterial species than boids without inflammatory disease (average 2.8 isolates).